BS EN IEC 62772. Composite hollow core station post insulators for substations with a.c. voltage greater than 1 000 V and d.c. voltage greater than 1 500 V. Definitions, test methods and acceptance criteria. (1st January 2021) - British Standards Institution,
No abstract available